2012
DOI: 10.1163/156853811x621508
|View full text |Cite
|
Sign up to set email alerts
|

The genetic crisis of the Mexican Bolson Tortoise (Gopherus flavomarginatus: Testudinidae)

Abstract: Gopherus flavomarginatus (Testudinidae) is endemic to a series of discontinuous, isolated basins collectively known as the Bolson de Mapimí in the Chihuahuan Desert. Its numbers declined after catastrophic levels of exploitation during the mid-20th century. However currently, the Bolson Tortoise appears to be on a path to recovery owing to intensive, sustained conservation efforts. We sequenced an 842-bp-long fragment of the D-loop from 76 individuals distributed throughout the species' range. The results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…The dearth of genetic diversity in our mtDNA results suggests that wild Bolson tortoises have experienced tremendous reductions in population size since at least the last glacial maximum. This is consistent with a recent study by Urena-Aranda and de los Monteros [44] who found 74 of 76 wild G. flavomarginatus sampled from throughout the Bolsón de Mapimí had the same mtDNA haplotype among only two identified in their study. The low level of STR allelic richness ( Table 3B ) and the limited genetic differentiation observed between the Appleton and Durango populations (F ST = 0.025) also support that the species has reduced genetic diversity.…”
Section: Discussionsupporting
confidence: 93%
“…The dearth of genetic diversity in our mtDNA results suggests that wild Bolson tortoises have experienced tremendous reductions in population size since at least the last glacial maximum. This is consistent with a recent study by Urena-Aranda and de los Monteros [44] who found 74 of 76 wild G. flavomarginatus sampled from throughout the Bolsón de Mapimí had the same mtDNA haplotype among only two identified in their study. The low level of STR allelic richness ( Table 3B ) and the limited genetic differentiation observed between the Appleton and Durango populations (F ST = 0.025) also support that the species has reduced genetic diversity.…”
Section: Discussionsupporting
confidence: 93%
“…Gopherus flavomarginatus (the Bolson tortoise) is endemic to a portion of the Mapimí Basin, in the Chihuahuan Desert, Mexico ( Fig 1 ). Widespread until the Pleistocene when it ranged from southern USA to central Mexico [ 22 ], several factors have brought the Bolson tortoise to the verge of extinction: climate changes in the Pleistocene-Holocene transition, recent anthropogenic activities, including habitat destruction due to overgrazing and agriculture, overexploitation for wildlife trade [ 23 – 26 ], and low genetic variation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%